2021
DOI: 10.3389/fcvm.2021.788645
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase 1 Exacerbating Aortic Dissection by Governing a Pro-Inflammatory Program in Macrophages

Abstract: Inflammation plays an important role in aortic dissection (AD). Macrophages are critically involved in the inflammation after aortic injury. Neuraminidases (NEUs) are a family of enzymes that catalyze the cleavage of terminal sialic acids from glycoproteins or glycolipids, which is emerging as a regulator of macrophage-associated immune responses. However, the role of neuraminidase 1 (NEU1) in pathological vascular remodeling of AD remains largely unknown. This study sought to characterize the role and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Recently, it was shown that NEU1 regulated toll-like receptor (TLR) activation on macrophages; specifically, ligand binding to TLRs induced NEU1 activity and led to receptor activation, nitric oxide and proinflammatory cytokine production [47]. Importantly, these NEU1 roles in macrophages are confirmed by several in vitro studies [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, it was shown that NEU1 regulated toll-like receptor (TLR) activation on macrophages; specifically, ligand binding to TLRs induced NEU1 activity and led to receptor activation, nitric oxide and proinflammatory cytokine production [47]. Importantly, these NEU1 roles in macrophages are confirmed by several in vitro studies [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 96%
“…These opposing functions of protein sialylation depend upon the target substrate molecules and the locations where the modification is regulated. Recent studies in mice using BM transplantation or monocyte-specific Cre-LoxP system have uncovered the key function of neuraminidases and sialyltransferases in monocytes and macrophages ( 80 , 90 , 94 , 120 , 123 ). More studies are needed to address the importance of protein sialylation using mice with additional tissue- and cell-type-specific targeting of the machinery, including endothelial cells and vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of cell surface sialylation to a normal level via exogenous NEU1 restored phagocytosis. NEU1 desialylates cell surface receptors such as Fc receptors for immunoglobulin G, and thus activates phagocytosis in macrophages and dendritic cells [ 73 , 74 ].…”
Section: Neuraminidases and Their Role In The Immune Systemmentioning
confidence: 99%
“…Since monocytes/macrophages feature the wound healing process as well as inflammatory processes, a balance between both is essential [ 105 , 106 , 107 , 108 ]. As described above, NEU1 promotes the pro-inflammatory phenotype of monocytes/macrophages [ 32 , 74 ] ( Figure 2 ), thereby affecting immune reactions and myocardial damage following an ischemic insult. It was recently shown that NEU1, upregulated early in the ischemic [ 27 ] and infarcted [ 109 ] area, significantly contributes to the development of heart failure following ischemia/reperfusion (I/R) injury in mice with a cardiomyocyte-specific overexpression of NEU1.…”
Section: Neuraminidases In the Context Of Cardiac Pathologiesmentioning
confidence: 99%